Question about Texas Instruments TI-84 Plus Calculator

Ad

[(3x-15)-(-12x+8)]-[(24-4x)]

3x-15-(-12x)+8-24-4x

15x-23-24-4x

19x-47

Posted on Nov 04, 2013

Ad

[3(x-5)-4(-3x+2)]-[4(6-x)]

[(3x-15)-(12x+8)]-(24-4x)

(-9x-23)-(24-4x)

-13x-(-1)

this is 9th grade stuff.

Posted on Sep 18, 2008

Ad

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

Best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of.(from cars to computers, handyman, and even drones)

click here to download the app (for users in the US for now) and get all the help you need.

Goodluck!

Posted on Jan 02, 2017

5x (-3x) = 2x -3x - -3x = 0

The equation then becomes 2x=10 2x/2 = x and 10/2 =5

then x=5. does it work 5x5=10+3*5 YES

The equation then becomes 2x=10 2x/2 = x and 10/2 =5

then x=5. does it work 5x5=10+3*5 YES

Jan 20, 2017 | The Office Equipment & Supplies

For 3x(7x+6x)=0, x=0

For 3x(7x+6x)=1, x=1/39

For 3x(7x+6x)=2, x=2/39

For 3x(7x+6x)=3, x=3/39 or 1/13

For 3x(7x+6x)=4, x=4/39

And so on...

For 3x(7x+6x)=1, x=1/39

For 3x(7x+6x)=2, x=2/39

For 3x(7x+6x)=3, x=3/39 or 1/13

For 3x(7x+6x)=4, x=4/39

And so on...

Jun 22, 2011 | Acer Aspire One Netbook

5x -2(x-2) = 6 -2(-3x-3)

5x -2x +4 = 6 +6x +6 (use the distributive property)

3x + 4 = 6x + 12 (collect terms)

4 = 3x + 12 (subtract 3x from both sides to get all x on one side)

-8 = 3x (subtract 12 from both sides to get only x on one side)

-8/3 = x (divide both sides by 3 to get x by itself)

Check

5(-8/3) -2((-8/3)-2) = 6 - 2(-3(-8/3)-3)

-40/3 -2(-8/3-6/3) = 6 - 2(8-3)

-40/3 -2(-14/3) = 6 -2(5)

-40/3 + 28/3 = 6 - 10

-12/3 = -4 (yes)

5x -2x +4 = 6 +6x +6 (use the distributive property)

3x + 4 = 6x + 12 (collect terms)

4 = 3x + 12 (subtract 3x from both sides to get all x on one side)

-8 = 3x (subtract 12 from both sides to get only x on one side)

-8/3 = x (divide both sides by 3 to get x by itself)

Check

5(-8/3) -2((-8/3)-2) = 6 - 2(-3(-8/3)-3)

-40/3 -2(-8/3-6/3) = 6 - 2(8-3)

-40/3 -2(-14/3) = 6 -2(5)

-40/3 + 28/3 = 6 - 10

-12/3 = -4 (yes)

Dec 19, 2010 | Answer Racing Ion Motorcycle Jersey 2010

(2x - 3y)(3x + 2y) = 2x*3x + 2x*2y - 3y*3x - 3y*2y

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

Dec 04, 2010 | Yahoo Computers & Internet

lim[x:+∞,√(x^(2)+3x-2)]-x

Oct 23, 2010 | Samsung Computers & Internet

I THINK YOU WANT TO KNOW THE VALUE OF X

X+4+2/3 = 6

(3X +12+2)/3 = 6

3X+14 = 3*6

3X + 14 =18

3X = 18 - 14

3X = 4

X = 4/3

X = 1.333 this is answer

X+4+2/3 = 6

(3X +12+2)/3 = 6

3X+14 = 3*6

3X + 14 =18

3X = 18 - 14

3X = 4

X = 4/3

X = 1.333 this is answer

Nov 04, 2009 | SoftMath Algebrator - Algebra Homework...

Do you mean "graph y=3x+x^2-3" or "solve 3x+x^2=3"?

To graph y=3x+x^-3 press Y=.

Type 3 ALPHA X + ALPHA X ^ 2 - 3 ENTER

Press GRAPH to see the graph.

To graph y=3x+x^-3 press Y=.

Type 3 ALPHA X + ALPHA X ^ 2 - 3 ENTER

Press GRAPH to see the graph.

Mar 21, 2009 | Texas Instruments TI-84 Plus Calculator

I am not quite sure what you are asking...

(1) if asking for graphing y= -2/3x+2, then press [diamond] [F1: Y=] type in .2/3x +2, see graph by [diamond][graph]

(2) if asking for graphing y= -2/3x+a, where a=3x, then first archive a=3x in Home screen by [home], type 3x [sto] a, then go back to y= menu, and type -2/3x+a in Y1

(3) if asking for graphing an equation that is dependent on 2 variables at the same time, use x-y-z axis (aka, change mode to graphing 3-D by [mode]graph [5:3D]) then enter desired equation in y= menu using Z function in terms of x and y aka z(x,y)= ...)

(1) if asking for graphing y= -2/3x+2, then press [diamond] [F1: Y=] type in .2/3x +2, see graph by [diamond][graph]

(2) if asking for graphing y= -2/3x+a, where a=3x, then first archive a=3x in Home screen by [home], type 3x [sto] a, then go back to y= menu, and type -2/3x+a in Y1

(3) if asking for graphing an equation that is dependent on 2 variables at the same time, use x-y-z axis (aka, change mode to graphing 3-D by [mode]graph [5:3D]) then enter desired equation in y= menu using Z function in terms of x and y aka z(x,y)= ...)

May 18, 2008 | Texas Instruments TI-89 Calculator

Just plug in one side of the equation and find the answer. Then plug in the other side and compare answers.

Feb 19, 2008 | Texas Instruments TI-89 Calculator

B. 2((2-Y)/3)-Y=3

2(2-Y)-Y=9

4-2Y-Y=9

-3Y=9-4

-3Y=5

-Y=5/3

Y=-1.67

A. 3X+(-1.67)=2

3X-1.67=2

3X=2+1.67

3X=3.67

X=3.67/3

X=1.22

2(2-Y)-Y=9

4-2Y-Y=9

-3Y=9-4

-3Y=5

-Y=5/3

Y=-1.67

A. 3X+(-1.67)=2

3X-1.67=2

3X=2+1.67

3X=3.67

X=3.67/3

X=1.22

Nov 05, 2007 | SoftMath Algebrator - Algebra Homework...

197 people viewed this question

Usually answered in minutes!

×